Examining multi-category cross purchases models with increasing dataset scale – An artificial neural network approach. (15th April 2019) - Yang, Zhiguo; Sudharshan, Devanathan
Highlights: Artificial Neural Network has advantages in multi-category purchase modeling. Demonstrated knowledge plugging- in Artificial Neural Network structure. Demonstrated extracting knowledge from Artificial Neural Network outcome. Knowledge plugging-in and extracting are promising future research. Abstract: Cross purchase modeling (cross model) is a method to simultaneously analyze multiple product categories for their interrelated influences on consumers' decisions to purchase each category. Traditional econometric modeling methods are hard to compute and complex in model specifications. This paper examines an artificial neural network (ANN) approach in this context. To understand ANN models' performance in increasing data scale, this paper uses four datasets of 4, 8, 16 and 32 categories to train ANN models and make predictions. Results show that an ANN model of 12 hidden nodes can be trained in about 3 h and make 88% prediction hit rate for the 16-category dataset. In contrast, a traditional econometric model requires more than 300 h to finish computing for the 16-category dataset. A typical critique of ANN technique is that it hides learned knowledge inside its model structure. This is a major obstacle preventing ANN from being more frequently applied in business research and practices. The current study takes two approaches to address this issue, i.e., (1) customizing ANN components to allow prior knowledge plugging in, and (2) using the generalized weight technique to reveal knowledge that is embedded in ANN training results. Findings of this paper help managers understand applicability of ANN technique in cross purchase model. By demonstrating plugging in prior knowledge to ANN model training and extracting knowledge from ANN training results, this paper shows approaches for understanding ANN embedded knowledge.